2019
DOI: 10.1186/s12913-019-4083-4
|View full text |Cite
|
Sign up to set email alerts
|

The 2010 expansion of activity-based hospital payment in Israel: an evaluation of effects at the ward level

Abstract: Background In 2010, Israel intensified its adoption of Procedure-Related Group (PRG) based hospital payments, a local version of DRG (Diagnosis-related group). PRGs were created for certain procedures by clinical fields such as urology, orthopedics, and ophthalmology. Non-procedural hospitalizations and other specific procedures continued to be paid for as per-diems (PD). Whether this payment reform affected inpatient activities, measured by the number of discharges and average length of stay (ALo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…10 Recent studies have shown that hospitals in different countries react differently to the adoption of DRGs and subsequent changes in prices. For example, in Israel the introduction of PRGs had no significant impact on ALoS and volumes of care at the ward (aggregate) level, 9 but in England volumes of care increased and ALoS decreased slightly. 30,31 In Italy, volumes of care increased for surgical but not for medical patients 32 while in Norway, volumes of care increased for medical but not for surgical patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Recent studies have shown that hospitals in different countries react differently to the adoption of DRGs and subsequent changes in prices. For example, in Israel the introduction of PRGs had no significant impact on ALoS and volumes of care at the ward (aggregate) level, 9 but in England volumes of care increased and ALoS decreased slightly. 30,31 In Italy, volumes of care increased for surgical but not for medical patients 32 while in Norway, volumes of care increased for medical but not for surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…The second is negotiations between HPs and hospitals that can set alternative reimbursement contracts, which supplant the official cap, and entail discounts that vary across HPs and hospitals. 5,9 Usually small hospitals or those located in areas with high density of hospitals give more discounts to HPs in order to attract them to refer patients. 8 Elective procedures performed in after-hours are paid PRG, and each hospital can decide whether to work in after-hours and what procedures to perform.…”
Section: Key Messagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings should be discussed considering several important characteristics of the Israeli health care system. Israel has a national health insurance financed predominantly via progressive taxation and includes four competing, non-profit health plans (HPs) which provide a broad package of services determined by the government [27,28]. The HPs provide care in the community and purchase hospital services for their members.…”
Section: Discussionmentioning
confidence: 99%
“…Israeli Arabs) it could be insufficient resulting in excessive use of hospital services. The occupancy rates of Israeli hospitals is one of the highest among the Organization for Economic Co-operation and Development (OECD) countries (greater than 90%) while the length of stay is one of the shortest (around 4 days) [27,28]. Furthermore, hospital pricing system is considered outdated and limits their reimbursement while pricing of novel procedures and technologies and rising.…”
Section: Discussionmentioning
confidence: 99%